Secondary battery diaphragm coating, secondary battery coated diaphragm, preparation method and secondary battery

By using secondary battery separator coatings prepared by specific ion exchange mica in electrochemical energy storage devices, the problems of high cost and poor performance of ceramic coating membranes are solved, low-cost and high-performance membranes are achieved, and the safety and power performance of electrochemical energy storage devices are improved.

CN119039827BActive Publication Date: 2025-04-22ZHONGKE (YIXING) NEW MATERIAL RES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411503354.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-04-22
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Existing ceramic-coated diaphragms have high cost and poor overall performance, making it difficult to meet the safety and power performance requirements of electrochemical energy storage devices.

Method used

Use secondary battery separator coatings containing specific ion exchange mica to improve the thermal stability, rate performance and cycle stability of the separator through the use of lithium ion or sodium ion exchange mica.

Benefits of technology

实现了低成本、高性能的二次电池隔膜,具备优良的热稳定性、低面密度、优异的倍率性能和循环稳定性,适合工业化应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039827B_ABST
    Figure CN119039827B_ABST
Patent Text Reader

Abstract

The invention discloses a secondary battery diaphragm coating, a secondary battery coated diaphragm, a preparation method and a secondary battery. The battery diaphragm coating comprises lithium ion exchange mica or sodium ion exchange mica; in the lithium ion exchange mica, Li + Content is 20000-60000 mg / Kg, Na + Content is 100-1000 mg / Kg, K + The content is 50-30000 mg / Kg; in the sodium ion exchange mica, Li + Content is 100‑800 mg / Kg, Na + Content is 2000-70000 mg / Kg, K + The content is 10-600 mg / Kg. The secondary battery separator of the present invention has excellent thermal stability and low surface density, low cost, and also has excellent rate performance and cycle stability when applied to batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a secondary battery diaphragm coating, a secondary battery coated diaphragm and a preparation method thereof, and a secondary battery. Background Art

[0002] Against the backdrop of carbon peak and carbon neutrality, the new energy industry has occupied an increasingly important position worldwide. According to public data, wind and solar power generation accounted for 15.3% of the total electricity consumption in society in 2023; the annual penetration rate of new energy vehicles in my country exceeded 33% in 2023. Driven by the demand for electric vehicle applications, electrochemical energy storage technology (especially lithium-ion batteries) has developed rapidly. In 2023 alone, electrochemical energy storage will be installed in 45GW of wind and solar power generation and 387.7GWh of new energy vehicles. However, with the iteration of electrochemical energy storage devices and systems, problems in safety, power performance, energy density, etc. have become increasingly prominent.

[0003] As an important component of electrochemical energy storage devices, the diaphragm plays the role of transmitting load ions and isolating electrons, and has an important impact on the performance of the device. At present, the mainstream diaphragms on the market are PP and PE diaphragms, which are low in cost but low in safety. They will shrink at high temperatures and cause short circuits between the positive and negative electrodes, thus causing safety problems. They will also affect the power performance due to poor wettability of the electrolyte. Ceramic-coated diaphragms can increase the temperature tolerance of the diaphragm and promote the infiltration of the electrolyte, thereby improving the safety and power performance of electrochemical energy storage devices. However, the coatings used in the current mainstream ceramic-coated diaphragms are mainly boehmite and alumina, which are high in cost, and the overall performance of the electrochemical energy storage devices constructed is poor. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the defects of high cost and poor comprehensive performance of ceramic coated diaphragms in the prior art, and provide a secondary battery diaphragm coating, a secondary battery coated diaphragm, a preparation method and a secondary battery. The secondary battery diaphragm of the present invention has excellent thermal stability and low surface density, low cost, and has excellent rate performance and cycle stability when applied to batteries.

[0005] The inventors of the present invention have discovered in their research that by applying ion exchange mica containing a specific ion content to a battery separator, the separator obtained not only has excellent thermal stability and a low surface density, but also has excellent rate performance and cycle performance. The ion exchange mica used contains rich energy carriers (Li ions or Na ions) and a low content of impure metal elements.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a secondary battery separator coating, comprising ion exchange mica, wherein the ion exchange mica is lithium ion exchange mica or sodium ion exchange mica;

[0008] Wherein, in the lithium ion exchange mica, Li + The content is 20000-60000 mg / Kg, Na + The content is 100-1000mg / Kg, K + The content is 50-30000 mg / Kg; in the sodium ion exchange mica, Li + The content is 100-800 mg / Kg, Na + The content is 2000-70000 mg / Kg, K + The content is 10-600 mg / Kg; mg / Kg refers to the mass of the target metal ion contained in each kilogram of ion exchange mica.

[0009] In the present invention, the lithium ion exchange mica has Li + The content is preferably 30000-60000 mg / Kg, for example 31460 mg / Kg, 41790 mg / Kg, 50113 mg / Kg, 50304 mg / Kg, 50550 mg / Kg, 51450 mg / Kg, or 51507 mg / Kg.

[0010] In the present invention, the lithium ion exchange mica has Na + The content is preferably 200-900 mg / Kg, for example 245 mg / Kg, 250 mg / Kg, 270 mg / Kg, 277 mg / Kg, 301 mg / Kg, 354 mg / Kg, 433 mg / Kg, 800 mg / Kg.

[0011] In the present invention, in the lithium ion exchange mica, K + The content is preferably 50-200 mg / Kg, for example 80 mg / Kg, 88 mg / Kg, 98 mg / Kg, 102 mg / Kg, 126 mg / Kg, 147 mg / Kg, 159 mg / Kg.

[0012] In the present invention, in the sodium ion exchange mica, Li + The content is preferably 200-600 mg / Kg, for example 546 mg / Kg.

[0013] In the present invention, the sodium ion exchange mica, Na + The content is preferably 40000-60000 mg / Kg, for example 57800 mg / Kg.

[0014] In the present invention, in the sodium ion exchange mica, K + The content is preferably 200-500 mg / Kg, for example 478 mg / Kg.

[0015] In the present invention, the lithium ion exchange mica or the sodium ion exchange mica is generally a sheet structure, the sheet diameter can be 1-5 μm, and the thickness can be 10-800 nm. The sheet diameter refers to the length of the mica sheet. The sheet-like mica sheet is more compatible with the two-dimensional structure of the base film. Compared with the coating material of spherical or irregular three-dimensional system particles, the utilization rate of the mica ceramic diaphragm is higher, and the surface density of the coated diaphragm to achieve the same effect is lower.

[0016] In the present invention, the preparation process of the ion exchange mica preferably includes the following steps: mixing the "lithium salt solution or sodium salt solution" and mica, and then subjecting the mixture to solid-liquid separation and drying.

[0017] The particle size D50 of the mica may be 0.5-5 μm, for example, 1 μm. The composition of the mica may include: 0-10.3% K 2 O, 0~5%Na 2 O, 0~8%Li 2 O, 0-30% MgO, 10-50% Al 2 O 3 、30~50%SiO 2 , 0~5%H 2 O, further, the mica may also include a small amount of Ca, Ti, Cr, Mn, Fe and F, etc., and % refers to the percentage of each component in the mass of the mica. The type of mica may be conventional in the art, generally one or more of muscovite, lepidolite, sericite, biotite, phlogopite, green mica and ferrolithium mica.

[0018] Wherein, during the ion exchange process, preferably, the mica is added into the "lithium salt solution or sodium salt solution".

[0019] Among them, lithium salt or sodium salt is selected for exchange according to different usage scenarios: when used in lithium-ion batteries, lithium salt solution is used for exchange to obtain lithium ion exchange mica; when used in sodium ion batteries, sodium salt solution is used for exchange to obtain sodium ion exchange mica.

[0020] The type of the lithium salt may be one or more of lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium perchlorate and lithium acetate. The concentration of the lithium salt solution may be 0.5-4M, for example 1M or 2M.

[0021] The type of the sodium salt may be one or more of sodium hydroxide, sodium carbonate, sodium chloride, sodium fluoride, sodium bromide, sodium iodide, sodium nitrate, sodium sulfate, sodium acetate, sodium oxalate and sodium citrate. The concentration of the sodium salt solution may be 0.5-4M, for example 1M or 2M.

[0022] Wherein, the mass ratio of the mica to the "lithium salt or sodium salt" may be 10:(0.3-4), for example, 10:0.5, 10:0.8, 10:1, 10:1.5 or 10:2.

[0023] The mixing treatment may be carried out by ultrasonic mixing or stirring mixing. The mixing treatment temperature may be 15-100° C., such as 25° C., 40° C. or 60° C., preferably 50-70° C. The mixing treatment time may be 0.5-48 h, such as 0.5 h, 2 h, 3 h or 4 h, preferably 1-6 h.

[0024] The solid-liquid separation may be carried out in a conventional manner in the art, such as filtration.

[0025] The drying method may be conventional in the art, such as baking. The baking temperature may be 50-200° C., preferably 70-100° C., such as 80° C. The baking time may be 12-30 hours, such as 24 hours.

[0026] In the present invention, the mass percentage of the ion exchange mica in the secondary battery separator coating may be 10%-40%, preferably 15%-30%, for example 20%.

[0027] In the present invention, the secondary battery separator coating preferably further comprises one or more of a dispersant, a binder and a wetting agent. The total amount of the dispersant, the binder and the wetting agent may account for 2%-15% by mass of the secondary battery separator coating, for example 4.6%.

[0028] In the present invention, the secondary battery separator coating preferably comprises the following raw materials: 10%-40% ion exchange mica, 0.1%-5% dispersant, 0.1%-10% binder, 0.02%-1% wetting agent, and the remainder is solvent, where % is the percentage of the mass of each component in the total mass of the secondary battery separator coating.

[0029] The dispersant may be one or more of polyacrylic acid, guar gum, polyacrylamide, sodium polyacrylate, polyethylene glycol 200, polyethylene glycol 400, N-methyl-2-pyrrolidone, N,N dimethylpyrrolidone, ethylene glycol and glycerol. The amount of the dispersant is preferably 0.5%-2%, such as 0.1%, 1% or 5%. By adding the dispersant, the mica can be more evenly distributed in the coating, avoiding local agglomeration, which is beneficial to further improve the mechanical properties, electrical properties, and high temperature properties of the electrochemical device.

[0030] Wherein, the type of the binder can be one or more of styrene butadiene, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polymethyl methacrylate, styrene butadiene rubber, lithium carboxymethyl cellulose, sodium methyl cellulose and sodium polyacrylate, such as styrene butadiene and carboxymethyl cellulose. The amount of the binder is preferably 2%-4%, for example 3.5%. In one embodiment, the binder is 3% styrene butadiene and 0.5% carboxymethyl cellulose. By adding the binder, the bonding between the coating and the base film can be made stronger, which is conducive to further improving the service life of the electrochemical device.

[0031] The wetting agent may be one or more of polysorbate 80, sorbitan laurate and polyoxyethylene-8-octylphenyl ether. The amount of the wetting agent is preferably 0.05%-0.2%, such as 0.02%, 0.1% or 1%. By adding the wetting agent, the mica can have a better affinity with the base film, which is convenient for coating preparation.

[0032] The solvent may be deionized water and / or N-methylpyrrolidone (NMP). The mass percentage of the solvent in the secondary battery separator coating may be 60%-95%, for example 75.4%. The content of the solvent may be appropriately selected according to the dispersibility of the mica. When the solvent content is too high, the slurry is too thin and the coating thickness obtained by one coating is limited. When the solvent content is too low, the viscosity is too high and it is not easy to coat. At the same time, the dispersibility of the mica in the slurry may not be high.

[0033] In a specific embodiment, the secondary battery separator coating is composed of the following raw materials: 20% ion exchange mica, 1% polyacrylic acid, 3% styrene butadiene, 0.5% carboxymethyl cellulose, 0.1% sorbitan laurate, and the balance is deionized water.

[0034] The present invention also provides a secondary battery separator, comprising a base film and a coating layer formed by coating the secondary battery separator coating as described above on the base film.

[0035] In the present invention, when the secondary battery separator is used for lithium ion batteries, the secondary battery separator coating uses lithium ion exchange mica; when the secondary battery separator is used for sodium ion batteries, the secondary battery separator coating uses sodium ion exchange mica.

[0036] In the present invention, the secondary battery separator coating is coated on at least one surface of the base film.

[0037] In the present invention, the type of the base film can be a polyethylene membrane, a polypropylene membrane, a polypropylene / polyethylene / polypropylene composite membrane, a polyvinylidene fluoride membrane, a poly(vinylidene fluoride-co-hexafluoropropylene) membrane, a glass fiber membrane, a cellulose composite membrane, a polyimide membrane or a polyamide membrane. The thickness of the base film can be 5-50 μm, for example, 9 μm. The base film can be obtained from conventional commercial products and can be cut into a desired shape before use. In order to improve the bonding strength between the base film and the coating, the base film can also be cleaned.

[0038] In the present invention, the thickness of the coating layer may be 0.5-10 μm, for example, 2 μm or 5 μm. The thickness of the coating layer may be comprehensively set according to the size of the electrochemical device, the load ions in the electrolyte, the use environment of the electrochemical device, the specific composition of the secondary battery separator coating, etc. However, if the coating layer is too thin, the effect of improving the thermal stability of the base film cannot be achieved; if the coating layer is too thick, the ion migration path is too long, resulting in obstruction of ion migration and excessive internal resistance of the battery.

[0039] The present invention also provides a method for preparing the secondary battery separator as described above, comprising the following steps: coating the secondary battery separator coating as described above on at least one surface of the base film and drying it.

[0040] In the present invention, the coating method can be a casting method, a spin coating method, a roller coating method or a dipping method.

[0041] In the present invention, the drying can be performed by heating at 40-80° C., or by drying in the shade at room temperature.

[0042] The present invention also provides a secondary battery, comprising a positive electrode, a negative electrode, an electrolyte and the secondary battery separator as described above. The secondary battery is preferably a lithium ion battery or a sodium ion battery.

[0043] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0044] The reagents and raw materials used in the present invention are commercially available.

[0045] The positive and progressive effects of the present invention are:

[0046] (1) The mica ceramic coated diaphragm of the present invention has excellent thermal stability, so the electrochemical device using the mica ceramic coated diaphragm has good safety;

[0047] (2) The mica ceramic coated diaphragm of the present invention has a low surface density due to its intrinsic layered structure, which matches the two-dimensional structure of the base film;

[0048] (3) The mica ceramic coated diaphragm of the present invention uses mica that has been exchanged with lithium / sodium ions, which contains rich carriers and has a low content of impurity metal elements in the mica, thereby making the rate performance and cycle stability of the lithium / sodium ion exchange mica coated diaphragm better;

[0049] (4) The mica ceramic coated diaphragm of the present invention uses low-priced raw materials, requires less coating material per unit area, can be coated with a water-based slurry, has a simple preparation process, and thus has low production costs and is suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a schematic diagram of the structure of the mica ceramic coated diaphragm of Example 1;

[0051] Figure 2 This is a schematic diagram of the structure of the mica ceramic coated diaphragm of Example 9;

[0052] Figure 3 The surface density of the commercial ceramic coated diaphragm (Comparative Example 3), the mica ceramic coated diaphragm prepared in Example 1, and the base film (Comparative Example 1);

[0053] Figure 4 The rate performance and cycle performance of the commercial ceramic coated diaphragm (Comparative Example 3) and the mica ceramic coated diaphragm prepared in Example 1;

[0054] Figure 5 Part (a) is an electron microscope photograph of the mica ceramic coated diaphragm prepared in Example 1; Figure 5 Part (b) is an electron microscope photograph of a commercial ceramic coated diaphragm (Comparative Example 3);

[0055] Figure 6 Rate performance and cycling stability of mica-coated separators at different lithium ion exchange degrees.

[0056] Description of reference numerals:

[0057] Basement membrane 100

[0058] Coating 200 DETAILED DESCRIPTION

[0059] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0060] The polyethylene (PE) base film used in the following examples and comparative examples has a thickness of 9 μm and is purchased from Enjie, model SV9; the composition (mass percentage) of the raw material mica used is: Li 2 O is 4.1%, Na 2 O is 0.2%, K 2 O is 4.3%, Al 2 O 3 43%, SiO 2 is 48.4%, particle size D 50 The particle size is 1 μm and was purchased from Jiangyin Qibang Pearlescent Materials Co., Ltd.; the polyacrylic acid aqueous solution was purchased from Adamas with the model number RG, Mw of 2000-5000 and a solid content of 50%; and the guar gum was purchased from Greagent with the model number AR.

[0061] Example 1

[0062] (a) Preparation of lithium ion exchange mica

[0063] Lithium chloride was dissolved in deionized water to prepare a 1M lithium chloride solution; mica was then added to the lithium chloride solution so that the mass ratio of mica to lithium chloride in the lithium chloride solution was 10:1, and the solution was ultrasonically treated at 25°C for 2h and then filtered. The obtained solid was baked at 80°C for 24h to obtain lithium ion exchange mica.

[0064] (b) Preparation of mica ceramic coated diaphragm

[0065] Firstly, polyethylene (PE) material was selected as the base film with a thickness of 9 μm; secondly, based on a total amount of 10 parts, lithium ion exchanged mica, polyacrylic acid in polyacrylic acid solution, styrene butadiene, carboxymethyl cellulose, sorbitan laurate and deionized water were mixed uniformly in a mass ratio of 2:0.1:0.3:0.05:0.01:7.54 to prepare a coating slurry; then, the prepared slurry was coated on one side surface of the PE base film by a gravure roller coating method to prepare a preform; finally, the prepared preform was placed at an ambient temperature of 60°C to dry, and cut into a desired shape for use, to obtain a composite ceramic coated diaphragm with a thickness of 11 μm.

[0066] (c) Lithium-ion battery preparation

[0067] The positive electrode sheet uses NMC811: the weight ratio of active material (NMC811), conductive agent Super P, adhesive polyvinylidene fluoride (PVDF) and carbon nanotube (CNT) is 96.5:0.5:2:1, and the surface density is 204g / m 2 , compaction 3.2g / cm 3 .

[0068] The negative electrode sheet is made of graphite: active material (graphite), conductive agent Super P, adhesive sodium carboxymethyl cellulose (CMC) and styrene butadiene (SBR) in a weight ratio of 95:0.2:3:1.8, with an area density of 100g / m 2 , compaction 1.5g / cm 3 .

[0069] Electrolyte: 1M LiPF 6 (lithium hexafluorophosphate), the solvent is EC (ethylene carbonate): DMC (dimethyl carbonate): EMC (ethyl methyl carbonate) = 1:1:1 (volume ratio), which contains 5% added fluoroethylene carbonate FEC (that is, the volume of FEC accounts for 5% of the total volume of the electrolyte).

[0070] The diaphragm is the mica ceramic coated diaphragm prepared in step (b). A 1Ah soft package is prepared by a lamination process.

[0071] Example 2

[0072] Compared with Example 1, except that the ion exchange temperature is adjusted to 40° C. during the preparation of lithium ion exchange mica, the other operations and conditions are the same as those in Example 1.

[0073] Example 3

[0074] Compared with Example 1, except that the ion exchange temperature is adjusted to 60° C. during the preparation of lithium ion exchange mica, the other operations and conditions are the same as those in Example 1.

[0075] Example 4

[0076] Compared with Example 1, except that the ion exchange time is adjusted to 0.5 h during the preparation of lithium ion exchange mica, the other operations and conditions are the same as those in Example 1.

[0077] Example 5

[0078] Compared with Example 1, except that the ion exchange time is adjusted to 4 hours during the preparation of lithium ion exchange mica, the other operations and conditions are the same as those in Example 1.

[0079] Example 6

[0080] Compared with Example 1, except that the mass ratio of mica to lithium chloride is adjusted to 10:2 during the preparation of lithium ion exchange mica, the other operations and conditions are the same as those in Example 1.

[0081] Example 7

[0082] Compared with Example 1, except that the mass ratio of mica to lithium chloride is adjusted to 10:0.5 during the preparation of lithium ion exchange mica, the other operations and conditions are the same as those in Example 1.

[0083] Example 8

[0084] (a) Preparation of lithium ion exchange mica

[0085] Lithium chloride was dissolved in deionized water to prepare a 1M lithium chloride solution; mica was then added to the lithium chloride solution so that the mass ratio of mica to lithium chloride in the lithium chloride solution was 10:2, and the solution was ultrasonically treated at 60°C for 4 hours and then filtered. The obtained solid was baked at 80°C for 24 hours to obtain lithium ion exchange mica.

[0086] (b) Preparation of mica ceramic coated diaphragm, same as Example 1.

[0087] (c) Preparation of lithium-ion battery, same as in Example 1.

[0088] Example 9

[0089] Compared with Example 1, except that the slurry is coated on both sides of the PE base film during the preparation of the mica ceramic coated diaphragm, the other operations and conditions are the same as those in Example 1.

[0090] Example 10

[0091] Preparation of sodium ion exchange mica: Sodium chloride is dissolved in deionized water to prepare a 1M sodium chloride solution; then mica is added to the sodium chloride solution so that the mass ratio of mica: sodium chloride is 10:1, and the solution is ultrasonically treated at 25°C for 2h and then filtered. The obtained solid is baked at 80°C for 24h to obtain sodium ion exchange mica.

[0092] Embodiment 11

[0093] (a) Preparation of lithium ion exchange mica, same as in Example 1.

[0094] (b) Preparation of mica ceramic coated diaphragm. Compared with Example 1, except that the amount of dispersant polyacrylic acid in the slurry was adjusted to 0.1%, the other operations and conditions were the same as those in Example 1.

[0095] (c) Preparation of lithium-ion battery, same as in Example 1.

[0096] Example 12

[0097] (a) Preparation of lithium ion exchange mica, same as in Example 1.

[0098] (b) Preparation of mica ceramic coated diaphragm: Compared with Example 1, except that the amount of dispersant polyacrylic acid in the slurry is adjusted to 5%, the other operations and conditions are the same as those in Example 1.

[0099] (c) Preparation of lithium-ion battery, same as in Example 1.

[0100] Example 13

[0101] (a) Preparation of lithium ion exchange mica, same as in Example 1.

[0102] (b) Preparation of mica ceramic coated diaphragm. Compared with Example 1, except that the amount of the wetting agent sorbitan laurate in the slurry was adjusted to 0.02%, the other operations and conditions were the same as those in Example 1.

[0103] (c) Preparation of lithium-ion battery, same as in Example 1.

[0104] Embodiment 14

[0105] (a) Preparation of lithium ion exchange mica, same as in Example 1.

[0106] (b) Preparation of mica ceramic coated diaphragm: Compared with Example 1, except that the amount of the wetting agent sorbitan laurate in the slurry is adjusted to 1%, the other operations and conditions are the same as those in Example 1.

[0107] (c) Preparation of lithium-ion battery, same as in Example 1.

[0108] Embodiment 15

[0109] (a) Preparation of lithium ion exchange mica, same as in Example 1.

[0110] (b) Preparation of mica ceramic coated diaphragm. Compared with Example 1, except that the dispersant in the slurry was replaced with 1% guar gum, the other operations and conditions were the same as those in Example 1.

[0111] (c) Preparation of lithium-ion battery, same as in Example 1.

[0112] Comparative Example 1

[0113] The operations and conditions for preparing the mica ceramic-coated separator and the lithium-ion battery are the same as those in Example 1, except that raw mica without ion exchange is directly used.

[0114] Comparative Example 2

[0115] Commercially available 9 μm polyethylene (PE) based film.

[0116] Comparative Example 3

[0117] Commercial ceramic coated diaphragm (9+3 μm), base film thickness 9 μm, coating 3 μm, purchased from Enjie, model SV9T30.

[0118] Effect Example

[0119] (1) Figure 1 and Figure 2 The mica ceramic coated diaphragm is provided with a base film 100, and a coating 200 is coated on the surface of the base film 100, wherein, according to actual application requirements, it can be as follows Figure 1 As shown, the coating 200 is applied to one side of the base film 100, or as shown in Figure 2 As shown, the coating 200 is coated on both sides of the base film 100. Lithium or sodium ion exchange mica is distributed in the coating 200. Therefore, when applied to an electrochemical device, the electrochemical device can have better rate capability because the carrier-rich ion exchange mica provides additional carriers. In addition, the mica ceramic coated diaphragm after ion exchange removes impurity metal ions, thereby further improving the service life of the electrochemical device. Mica coated on the base film can also improve the thermal stability of the base film, thereby improving the safety of the electrochemical device.

[0120] (2) Mica element analysis

[0121] The metal ions in mica that can act as charge carriers and affect electrochemical performance are mainly Li + 、Na + , K + The results of ICP analysis of the elements of the mica used in Examples 1-8 and Example 10 before and after lithium ion exchange are shown in Table 1.

[0122] The results show that the mica before exchange contains a large amount of K + , followed by Li + , and a certain amount of Na + . K + and Na + The presence of may have a negative impact on lithium-ion batteries (similarly, Li + and K + After ion exchange, the content of the exchanged ions increased significantly, while the content of other impurity ions decreased significantly. + After the exchange, Li + Increased from 19321 mg / Kg to 48217 mg / Kg, Na + From 1517 mg / Kg to 301 mg / Kg, K+ From 61272 to 126 mg / Kg. Similarly, in Example 10, after sodium ion exchange, Na + From 1517mg / Kg to 57800mg / Kg, while Li + From 19321mg / Kg to 546mg / Kg, K + From 61272mg / Kg to 478mg / Kg.

[0123] Table 1 Mica in Li + Analysis of ICP test results before and after ion exchange

[0124]

[0125] Note: Element content refers to the mass of the element to be tested contained in each kilogram of ion exchange mica.

[0126] (2) Analysis of thermal stability of diaphragm

[0127] The thermal stability of the separator is evaluated by the thermal shrinkage rate of the separator. The test method reference standards include "GB / T 12027-2004 Plastics-Film and Sheet-Heating Dimensional Change Test Method" and "UL 2591-2009 Outline of Investigation For Battery Separators". The specific test method is to cut the separator into 3 x 1.5 cm 2 The strips were then placed between two glass plates and heated in an oven at 130°C for 0.5 h before being taken out to measure the dimensional change rates of the membrane in the length and width directions. The length direction of the wound membrane is called the machine direction (MD), and the width direction is called the transverse direction (TD). In the experiment, the original size of the MD was set to 3 cm, and the original size of the TD was set to 1.5 cm.

[0128] The experimental results are shown in Table 2. The MD and TD of the base film have a thermal shrinkage rate of 17% and 9% at 130°C, and a thermal shrinkage rate of 88% and 85% at 150°C. After coating with mica ceramic, the thermal shrinkage rates are reduced to 1.3% and 0.9% (Example 1, lithium ion exchanged mica), 2% and 1.3% (Comparative Example 1, mica without lithium ion exchange), respectively. This shows that mica ceramic separator can greatly improve the thermal stability of the separator, thereby improving the safety of lithium-ion batteries.

[0129] Table 2 Base film (Comparative Example 2) and mica coated diaphragm

[0130]

[0131] (3) Diaphragm surface density analysis

[0132] The mass of the commercial ceramic coated diaphragm (Comparative Example 3), the mica ceramic coated diaphragm in Example 1 and the base film (Comparative Example 2) with the same area was weighed, and the surface density was obtained by mass / area. Figure 3 , the surface density of the mica coated diaphragm in Example 1 is 7.5 g / m 2 , while the commercial separator is 9.3g / m 2 , the surface density is reduced by 20%.

[0133] The electrochemical properties of the commercial ceramic-coated separator and the mica ceramic-coated separator in Example 1 were compared (eg Figure 4 ). The results show that the mica ceramic coated diaphragm has better rate performance, which is 81mAh / g at 10C, while the commercial ceramic coated diaphragm is 40mAh / g, which is 100% higher than the latter; and the cycle performance of the two is equivalent. This shows that the reduction in surface density does not deteriorate the performance of the mica coated diaphragm, but can reduce the amount of materials used and save costs.

[0134] From the electron microscopy image ( Figure 5 ) From the perspective of the mica coated diaphragm, the mica coated diaphragm is mostly composed of flake particles, while the commercial ceramics are mostly irregular three-dimensional bulk structures. There is reason to believe that the bulk structure leads to low material utilization, which reduces the material utilization rate, resulting in high surface density and poor performance.

[0135] (4) Electrochemical performance test (rate performance and cycle performance)

[0136] The rate performance and cycle performance of the mica coated separators prepared in Examples 1-8, Examples 11-15 and Comparative Example 1 were tested, and the charge and discharge cut-off voltage was 2.5-4.2V. The test results are shown in Tables 3 and Figure 6 .

[0137] The capacity retention rate of Example 1 at 5C is 0.84Ah / 1Ah = 84%, while that of Comparative Example 1 is 0.75Ah / 1Ah = 75%; the number of cycles of 80% capacity retention rate of Example 1 at 1C cycle is 627, while that of Comparative Example 1 is 270. The above results show that after lithium ion exchange, the rate performance and cycle performance are better. Combined with the results of (1) mica element analysis, it may be because K + and Na + The presence of + The transport of Na / Na in the electrolyte and interface affects the kinetic performance of lithium-ion batteries. + , K / K + The electrode potential ratio Li / Li + High (E Li =–3.04 V, E Na =–2.71 V, EK =–2.94 V vs. SHE), which makes it easy for sodium and potassium dendrites to deposit on the negative electrode surface and pierce the separator. At the same time, they will also react with the electrolyte, leading to electrolyte depletion. A combination of factors leads to accelerated battery failure.

[0138] Table 3 Rate performance and cycle performance of mica coated separator

[0139]

[0140] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A secondary battery separator coating, characterized in that: It includes 10%-40% ion exchange mica, 0.5%-2% dispersant, 0.1%-10% binder, 0.05%-0.2% wetting agent, and the balance is solvent, where % is the percentage of the mass of each component to the total mass of the secondary battery separator coating; The ion exchange mica is lithium ion exchange mica or sodium ion exchange mica; in the lithium ion exchange mica, Li + The content is 30000-60000mg / Kg, Na + The content is 200-900mg / Kg, K + The content is 50-30000mg / Kg; in the sodium ion exchange mica, Li + The content is 200-600mg / Kg, Na + The content is 40000-60000mg / Kg, K + The content is 10-600 mg / Kg; mg / Kg refers to the mass of the target metal ion contained in each kilogram of ion exchange mica; The preparation process of the ion exchange mica comprises the following steps: mixing the "lithium salt solution or sodium salt solution" and mica, separating the solid from the liquid, and drying; the mass ratio of the mica to the "lithium salt or sodium salt" is 10:(0.3-4); the temperature of the mixing treatment is 15-100°C, and the time of the mixing treatment is 1-6h; The dispersant is one or more of polyacrylic acid, polyacrylamide, sodium polyacrylate, polyethylene glycol 200, polyethylene glycol 400, N-methyl-2-pyrrolidone, N,N-dimethylpyrrolidone, ethylene glycol and glycerol.

2. The secondary battery separator coating according to claim 1, characterized in that: In the lithium ion exchange mica, K + Content is 50-200mg / Kg; And / or, in the sodium ion exchange mica, K + The content is 200-500mg / Kg.

3. The secondary battery separator coating according to claim 1, characterized in that: The preparation process of the ion exchange mica satisfies one or more of the following conditions: (1) The particle size D50 of the mica is 0.5-5 μm; (2) The composition of the mica includes: 0-10.3% K2O, 0-5% Na2O, 0-8% Li2O, 0-30% MgO, 10-50% Al2O3, 30-50% SiO2, 0-5% H2O; (3) The type of the lithium salt is one or more of lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium hydroxide, lithium carbonate, lithium nitrate, lithium sulfate, lithium perchlorate and lithium acetate; (4) The concentration of the lithium salt solution is 0.5-4M; (5) The sodium salt is one or more of sodium hydroxide, sodium carbonate, sodium fluoride, sodium bromide, sodium iodide, sodium chloride, sodium nitrate, sodium sulfate, sodium acetate, sodium oxalate and sodium citrate; (6) The concentration of the sodium salt solution is 0.5-4M.

4. The secondary battery separator coating according to claim 1, characterized in that: The total amount of the dispersant, the binder and the wetting agent accounts for 2% to 15% by mass of the secondary battery separator coating.

5. The secondary battery separator coating according to claim 1, characterized in that: The raw materials meet one or more of the following conditions: (1) The binder is one or more of styrene butadiene, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polymethyl methacrylate, styrene butadiene rubber, lithium carboxymethyl cellulose, sodium methyl cellulose and sodium polyacrylate; (2) The amount of the binder is 2%-4%; (3) The wetting agent is one or more of polysorbate 80, sorbitan laurate and polyoxyethylene-8-octylphenyl ether; (4) The solvent is deionized water and / or N-methylpyrrolidone; (5) The mass percentage of the solvent in the secondary battery separator coating is 60%-95%.

6. A secondary battery separator, characterized in that: The invention comprises a base film and a coating layer formed by coating the secondary battery separator coating according to any one of claims 1 to 5 on the base film.

7. A method for preparing a secondary battery separator as claimed in claim 6, characterized in that: The method comprises the following steps: coating the secondary battery separator coating on at least one side of the base film and drying the coating.

8. A secondary battery, characterized in that: The secondary battery comprises a positive electrode, a negative electrode, an electrolyte and the secondary battery separator as claimed in claim 6.

Citation Information

Patent Citations

  • Safety diaphragm as well as preparation method and application thereof

    CN117410652A